2015
DOI: 10.1186/s40662-015-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Collagen cross-linking: when and how? A review of the state of the art of the technique and new perspectives

Abstract: Since the late 1990s corneal crosslinking (CXL) has been proposed as a new possibility to stop progression of keratoconus or secondary corneal ectasia, with the promising aim to prevent progressive visual loss due to the evolution of the pathology and to delay or avoid invasive surgical procedures such as corneal transplantation. The possibility of strengthening corneal tissue by means of a photochemical reaction of corneal collagen by the combined action of Riboflavin and ultraviolet A irradiation (UVA), radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 143 publications
2
59
1
9
Order By: Relevance
“…Briefly, during this procedure the corneal epithelium is removed and riboflavin eye drops are applied for a pre-defined time-period followed by corneal exposure to ultraviolet A (UVA) light. This induces a photochemical reaction leading to an increase in cross-linking of the extracellular matrix and thereby to an increase in corneal rigidity [75]. Since CXL is used to prevent progression of keratoconus, patients at risk should be identified as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, during this procedure the corneal epithelium is removed and riboflavin eye drops are applied for a pre-defined time-period followed by corneal exposure to ultraviolet A (UVA) light. This induces a photochemical reaction leading to an increase in cross-linking of the extracellular matrix and thereby to an increase in corneal rigidity [75]. Since CXL is used to prevent progression of keratoconus, patients at risk should be identified as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, corneal collagen crosslinking (CXL) has gained popularity for the treatment of progressive corneal ectasia 1. CXL has been reported to slow down the rate of progression of corneal ectasia in the setting of keratoconus and pellucid marginal degeneration,2–4 ectasia after laser in situ keratomileusis and photorefractive keratectomy,5 6 ectasia after radial keratotomy7 and ectasia in paediatric populations 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have shown better results with standard 30 minutes irradiation protocol, as recommended by Wollensak et al initially 10,11. However, accelerated CXL has also shown promise, which uses higher irradiance in lesser time to obtain desired results 12. Kir MB et al in their study on 48 eyes showed stabilization of BCVA and corneal topographical indices with irradiance of 45mW/cm2 for two minutes after two years 13.…”
Section: Discussionmentioning
confidence: 99%